OP0307 No Long-Term Effect on Disease Activity and Pain of Physical Activity Found in Prospective Observational Study of Early Rheumatoid Arthritis. (15th July 2016) - Sandberg, M.E.; Westerlind, H.; Saevarsdottir, S.; Frumento, P.; Klareskog, L.; Alfredsson, L.
Abstract : Background: Physical activity was once perceived as potentially harmful for patients with rheumatoid arthritis (RA), but intervention trials in the past decade have shown that physical activity on the contrary is well tolerated in established RA. [1] Further, small, short-term intervention studies have in addition shown potential positive effects of physical activity/exercise on the symptoms of RA [2]. Objectives: Prospectively investigate the long-term effect of physical activity on the prognosis of rheumatoid arthritis (RA) in terms of disease activity, measured as DAS28, and pain, measured on the VAS-scale. Methods: We used incident RA cases from the population-based EIRA-study with clinical follow-up in the Swedish Rheumatology Quality Register (2006–2010). We investigated the effect of self-reported physical activity 1 year after diagnosis (>150 min. of moderate/intense or >75 min intense activity/week), on the probability of remission (DAS28<2.6) and remaining pain (CRP<10mg/l and VAS-pain>20mm) after 3 years, using modified Poisson regression, adjusted for sex, age at diagnosis, BMI, education, smoking, physical activity before diagnosis and baseline level of DAS28/pain, respectively. Further, we estimated the longitudinal effect from assessment of physical activity, using mixed models, and also the effect of the combination of physical activity 5 years before/1 year after diagnosis in four groups (low-low, low-high, high-low and high-high). Results: 555 RA-patients were included in this study, the mean age at diagnosis was 54 years and 74% was female. One year after diagnosis, when physical activity was assessed, the mean DAS28 was 2.92 and the mean VAS-pain was 30. We could not detect any effect of physical activity after diagnosis; the adjusted risk ratio for remission was 1.07 (95%CI:0.74–1.53) and for remaining pain 1.12 (95%CI:0.75–1.67). Similarly, no effect was found using longitudinal analysis (p-value for difference in DAS28, comparing active and non-active patients: 0.32, corresponding p-value for difference in VAS-pain: 0.71) or when we investigated the combination pattern of physical activity 5 years before RA-diagnosis and 1 year after. Conclusions: In this prospective cohort study we did not find evidence of an effect of self-reported physical activity on the prognosis of RA, either measured as pain or disease activity. Such lack of improvement could e.g. occur if the effect of physical activity would be short-lasting. There is no reason to doubt the beneficial effect of physical activity on the general health of RA-patients, similar to the effect for the general population. References: Ottawa Panel Evidence-Based Clinical Practice Guidelines for Therapeutic Exercises in the Management of Rheumatoid Arthritis in Adults. 2004 Stenstrom CH, Minor MA. Evidence for the benefit of aerobic and strengthening exercise in rheumatoid arthritis. Arthritis Rheum. 2003 Jun 15; 49(3):428–434. Disclosure of Interest: None declared